Real‐time ultrasound virtual navigation in 3D PET/CT volumes for superficial lymph‐node evaluation: innovative fusion examination. (6th October 2021) - Garganese, G.; Bove, S.; Fragomeni, S.; Moro, F.; Triumbari, E. K. A.; Collarino, A.; Verri, D.; Gentileschi, S.; Sperduti, I.; Scambia, G.; Rufini, V.; Testa, A. C.
ABSTRACT: Objective: To evaluate the feasibility and clinical application of fusion imaging with virtual navigation, combining 18 F‐fluorodeoxyglucose ( 18 F‐FDG) positron emission tomography/computed tomography (PET/CT) with real‐time ultrasound imaging, in assessing superficial lymph nodes in breast‐cancer and gynecological‐cancer patients. Methods: This was a pilot study of breast‐ and gynecological‐cancer patients with abnormal uptake of 18 F‐FDG by axillary or groin lymph nodes on PET/CT scan, examined at our institution between January 2017 and May 2019. Fusion imaging was performed, uploading preacquired PET/CT DICOM images onto the ultrasound machine and synchronizing them with real‐time ultrasound scanning performed at the lymph‐node site. In the first phase, we assessed the feasibility and reliability of fusion imaging in a series of 10 patients with suspicious lymph nodes on both PET/CT and ultrasound, and with full correspondence between both techniques in terms of size, shape and morphology of the lymph nodes (Group A). In the second phase, we included 20 patients with non‐corresponding findings between PET/CT and ultrasound: 10 patients with lymph nodes that were suspicious or pathological on PET/CT scan but not suspicious on ultrasound assessment (Group B), and 10 patients with suspicious or pathological lymph nodes on both PET/CT and ultrasound but with no correspondence between the two techniques in terms of number of affected lymph nodes (Group C). Results: In the 30 selected patients, fusion imaging was assessed at 30 lymph‐node sites (22 inguinal and eight axillary nodes). In the first phase (Group A), the fusion technique was shown to be feasible in all 10 lymph‐node sites evaluated. In the second phase, fusion imaging was completed successfully in nine of 10 cases in Group B and in all 10 cases in Group C. In all groups, fusion imaging was able to identify the target lymph node, guiding the examiner to perform a core‐needle aspiration biopsy or to inject radiotracer for selective surgical nodal excision, according to the radio‐guided occult lesion localization technique. Conclusion: Fusion imaging with virtual navigation, combining PET/CT and real‐time ultrasound imaging, is technically feasible and able to detect target lymph nodes even when PET/CT and ultrasound findings are inconsistent. Fusion imaging can also be used to guide the performance of core‐needle aspiration biopsy, avoiding further surgical diagnostic procedures, or the injection of radiotracer for selective surgical nodal excision, enabling more sparing, selective surgery. This innovative technique could open up multiple diagnostic and therapeutic opportunities in breast and gynecological oncology. © 2021 International Society of Ultrasound in Obstetrics and Gynecology.